Physicochemical, Nutritional and Processing Properties of Promising Newly Bred White and Yellow Fleshed Cassava Genotypes in Nigeria - Ukenye, E.; Ukpabi, U.J.; Chijoke, U.; Egesi, C.; Njoku, S. (Pakistan Journal of Nutrition, 2013)
Randomly selected fresh roots of sixteen experimental cassava cultivars (fourteen improved cultivars and two controls) in National Root Crops Research Institute, Umudike, Nigeria were assessed for their food quality characteristics amongst other relevant pre and post harvest traits. TMS 30572 and TME 419 cultivars of cassava were used as local and national checks or controls. The result of the physical properties of the experimental roots showed that those with yellow and cream pulp have high carotene content which is a precursor of Vit.A. The proximate composition result of the experimental energy rich roots showed that ten of the genotypes (like the control cultivars) have high Dry Matter (DM) content of above 30%; with nine genotypes having high protein content above 3% like the controls also. Seven of the new genotypes also have starch content of >20%, with only four of them having relatively high carotenoid of > 3 μg/g when compared with the control. It was observed also from this study that the yellow fleshed cassava gari look similar to the yellow gari (cassava+oil) found in Nigerian local market.